Micro-flower-like MoS2-modified Co9S8 heterostructure as anode material for sodium-ion batteries with superior reversibility and rate capacity. (10th May 2023) - He, Yang; Liu, Changlin; Peng, Shang; Zhang, Juan; Chen, Gang; Feng, Zhongbao; Zhao, Qiang; Abudula, Abuliti; Guan, Guoqing
Highlights: Micro-flower-like MoS2 -modified Co9 S8 is fabricated as anode material for SIBs. The obtained anode shows enhanced capacity with cycling. The anode exhibits exceptional reversibility and rate capacity. The anode has rich active sites, high-speed charge transfer and low energy barrier. Abstract: Designing and fabricating of heterostructured materials with long-term cycling stability and high-rate capacity for the anode of sodium-ion batteries (SIBs) still remain a great challenge. Herein, micro-flower-like MoS2 -modified Co9 S8 (Co9 S8 /MoS2 ) with a three-dimensional (3D) heterostructure was first obtained via a simple solvothermal synthesis followed by a solid sulfidation treatment process. As a material for the anode of SIBs, the Co9 S8 /MoS2 -based electrode with an initial Co/Mo molar ratio of 1/1 (denoted as CM55-S) exhibits the best sodium storage performance with a boosted capacity, superior reversibility (424.5 mAh g –1 @2 A g –1 at the 1600th cycle, 401.1 mAh g –1 @5 A g –1 at the 800th cycle), and an excellent rate capacity (210.1 mAh g –1 @20 A g –1 ). Density functional theory (DFT) calculations confirm that the Co9 S8 /MoS2 heterostructure has a lower energy barrier (0.30 eV) than the pure Co9 S8 (0.53 eV). It is expected that such a heterostructured material could be an attractive candidate as the material of the anode for SIBs.